PERBANDINGAN PENURUNAN KONSOLIDASI METODE TERZAGHI DENGAN ASAOKA PADA VACUUM PRELOADING - Fina Mayumi Boangmanalu; Istiatun Istiatun (Politeknik Negeri Jakarta, 2023)
Around 20 million hectares of Indonesia's total land area, or more than 10%, has soft soil. Soft soils can be problematic in construction projects due to their low bearing capacity, high water content, limited permeability, and high compressibility. Vacuum preloading, a technique to hasten consolidation by employing atmospheric pressure from the vacuum as a surcharge load, is one of the improvements for soft soil. The Terzaghi method is typically used to calculate the prediction of the final settlement and the time to reach the final settlement, however the forecast of settlement by the Terzaghi method produces better results than the actual settlement. To estimate the final settlement that takes place in the field, a method with a reliable level of accuracy is used—the Asaoka method. The main goals of this analysis are to determine the final settlement using the Asaoka method, the time needed to reach the final settlement using the Asaoka method, the degree of consolidation caused by vacuum preloading, and soil parameters that support notable differences between the Terzaghi method and Asaoka method using back analysis. According to both site reviews, the Terzaghi method produced settlement outcomes that were 36% and 79% higher than those obtained using the Asaoka method. The time required to reach 90% consolidation on both site reviews are 252 days and 196 days. The results of the Asaoka method used to calculate the degree of consolidation on both site reviews are 92.33% and 94.47%. The value of compression index (Cc), which was derived by back analysis calculations, is what most strongly supports the significant outcomes between the Terzaghi method and the Asaoka method.